Advantages of Project-Based Technologies in Enhancing Biology Education - Hamidova Dildora Haqqul qizi; Sullieva Suluv Khurramovna (American Journal of Biomedicine and Pharmacy, 2025)
This article explores the advantages of using project-based learning (PBL) technologies to improve the quality and effectiveness of biology education. Project-based learning is a student-centered instructional approach that emphasizes active inquiry, collaboration, and real-world application of knowledge. By integrating PBL into biology lessons, students are encouraged to develop critical thinking, problem-solving, and research skills. Furthermore, project-based activities help learners connect theoretical biological concepts with practical situations, making the learning process more engaging and meaningful. The article discusses how the use of technology and interdisciplinary approaches within PBL frameworks enhances student motivation and academic performance. Several successful examples and methodological recommendations for implementing project-based technologies in biology classrooms are also presented.